To develop computer programming on aircraft aerodynamic characteristics estimation / [microform] - Jayaprakash Saththasivam (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Kejuruteraan Mekanikal (Aeronautik)) - Universiti Teknologi Malaysia, 2005